Enhance Administration Of Legal Assistance Program For Community Is Disable To Seeking Justice Based On Law Number 16 Year 2011 About Legal Assistance - Marcos Sihombing; Tommy Leonard; Elvira Fitriyani Pakpahan (CV. Inara, 2021)
The implementation of the Legal Aid Post (Posbakum) by the District Court includes 3(three) scopes of legal services by the provisions contained in Perma No. 1 of 2014. The three scopes are fee waiver services, and holding hearings outside the court building, and providing Court Posbakum. In connection with the implementation of this Posbakum, the District Court only provides room facilities to Posbakum for three accredited legal aid institutions or advocate organizations. The handling of legal aid funds for each case will be submitted by the Court through the Local Office of the Ministry of Law and Human Rights. However, this does not mean that the function of the facilitator can be ignored, considering that this Posbakum is located in the Constitutional Court, it is necessary to pay attention to the special mandate from the State Administrators to the Constitutional Court to ensure the success of free legal services for the poor. . Therefore, it is also hoped that the presence of Posbakum in the Constitutional Court can erode the negative and frightening stigma of the Court for the wider community. Learn more about this source text required source text for additional translation information Law enforcement on the one hand and justice in society on the other hand requires harmony, especially in the right to obtain legal assistance for the community without discriminating against race, religion, and group. As for the formulation of the problem, Research methods which is used by researchers as using an empirical juridical approach.